PyHTStack2D: A Python package for high-throughput homo/hetero stacking of 2D materials - Zhang, Qian; Yang, Jinlong; Hu, Wei (Computer physics communications, 2025)
Two-dimensional (2D) van der Waals (vdWs) structures are the subject of extensive research in materials science, celebrated for their unique physical properties and potential technological applications. However, the diversity of stacking modes in 2D vdWs structures poses a challenge for research. In response to the complexity of the stacking process for these layered structures, we have developed a Python package, PyHTStack2D, specifically designed to support High-Throughput Stacking of 2D materials research. The package provides two primary functionalities: Firstly, it facilitates the batch stacking of homo- and heterostructures, with careful consideration of specific sequences and patterns, such as those observed in the 1T/2H phase transitions of transition metal dichalcogenides; Secondly, it aids in the efficient creation of computational directories and the generation of requisite shell scripts for the batch computation submissions of the stacked structures. By employing this package, we performed high-throughput computational simulations of properties such as electronic energy band structures and magnetic ground states of bilayers composed of 2H-TMDHs. These results have enabled us to identify the types of electronic band structures within these systems, providing critical insights into their potential applications in optoelectronics and photocatalysis. Furthermore, preliminary findings indicate the potential feasibility of generating bipolar magnetic semiconductors via the stacking of magnetic monolayers. The PyHTStack2D package provides an opportunity to perform efficient high-throughput calculations of 2D vdWs homo/heterostructures. Program Summary Program title: PyHTStack2D CPC Library link to program files:https://doi.org/10.17632/n94n2zcxdr.1 Developer's repository link:https://github.com/QianZhang21/pyhtstack2d-master Licensing provisions: BSD 3-clause Programming language: Python 3, Bash (shell) Nature of problem: Implement the theoretical calculations of 2D layered materials, focusing on the challenges posed by the diversity of stacking modes. While stacking these layers to form homo/heterostructures can overcome some limitations inherent to monolayers, the variety of possible configurations introduces significant complexity. This complexity must be incorporated into research to enable accurate modeling and facilitate further studies on these materials, ensuring that the unique properties of different stacking arrangements are properly understood and effectively utilized. Solution method: The Python package, PyHTStack2D, is used to perform high-throughput stacking of 2D vdW homo/heterostructures. It accounts for various stacking patterns in specific systems and considers different stacking sequences, such as a Janus-TMD monolayer that is asymmetric in the vertical direction. By flipping the monolayer in the Z-direction before stacking, different bilayer structures can be generated. PyHTStack2D also assists in generating shell scripts for high-throughput first-principles calculations, facilitating large batch computations.